Research on cuttings and flower yield improvement of marigold cv. Siracole for sustainable production through Jeevamrit application - Nitesh Kaushal; Bharati Kashyap; Balbir Singh Dilta (Heliyon)
A sustainable approach of farming involves using desi-cow waste products helps to improve soil biology. Jeevamrit, a traditional biofertilizer, enhances soil health and organic carbon and also reduces the need for farmyard manure, hence minimizing carbon footprint and supports eco-friendly agriculture. The present study investigated the effectiveness of Jeevamrit compared to chemical fertilizers and growth regulators for maintaining a healthy mother block of marigold. Jeevamrit was applied at a rate of 2 L per square meter every 15 days in the mother block. A comprehensive evaluation of seven nutritional and growth regulator modules was conducted across five harvesting flushes (H1, H2, H3, H4, and H5), with subsequent planting occurring in both summer and winter, and vegetative parameters compared to other treatments. Comparing cuttings from various treatments, Jeevamrit-treated plants had higher diameter (3.64 mm), rooting percentage (77.62 %), roots per cutting (35.46), survival rate (81.59 %), faster rooting (14.90 days), the microbial analysis shows a higher microbial population i.e. bacterial (18.27 × 105 cfu g−1 Soil), fungal (3.64 × 103 cfu g−1 Soil), and actinomycetes (3.12 × 103 cfu g−1 Soil) in soil and a higher uptake of N (17.73 kg ha −1), P (9.48 kg ha −1), and K (15.03 kg ha −1) by plants resulting into better growth and development. Yet, the highest cutting yield per plant (92.92) and m−2 (826.64) was observed with foliar application of benzyl adenine @ 100 ppm combined with N-P-K @ 30:20:20 g/m2. Among the harvesting flushes, H4 yielded the highest number of cuttings per plant (109.39) and per square meter (973.34). In contrast, H1 achieved the best results for rooting percentage (81.90 %), number of roots per cutting (29.78), survival percentage (78.07 %), and the shortest rooting time (14.49 days). Additionally, H3 showed the highest microbial activity, with viable bacterial counts at 14.38 × 105 cfu g−1, fungal counts at 3.56 × 103 cfu g−1, actinomycetes at 2.84 × 103 cfu g−1, and organic carbon content at 0.97 %. Under the second experiment the plants grown under natural farming produce more number (0.76 %) and yield of marketable flowers per plant (3.77 %) over recommended dose of fertilizers. The study concludes that while Jeevamrit significantly enhances plant growth and soil health, the combination of benzyl adenine with a balanced N-P-K fertilizer results in higher cutting yield. Moreover, Jeevamrit has been identified as an effective alternative to chemical fertilizers for the cultivation of marigold, specifically in the production of cuttings and flowers.